Strategies for Optimizing Radiation Therapy for Small Cell Lung Cancer - Mosley, Mary (MD Conference Express, 2015)
The current evidence for the optimal delivery of radiation therapy in patients with small cell lung cancer is reviewed in this article. Hippocampal avoidance prophylactic cranial irradiation is being studied to reduce the associated neurocognitive deficits. Thoracic radiation therapy combined with prophylactic cranial irradiation was shown to improve overall survival and progression-free survival and reduce intrathoracic progression in the CREST trial.